Transcending the Boundaries of Human and AI Being: A Posthuman Study of Kazuo Ishiguro’s Novel Klara and the Sun - Chapai, Udaya (Pragnya Sarathi प्रज्ञा-सारथि, 2024)
This study critically examines the relationship between humans and AI beings in Kazuo Ishiguro's novel Klara and the Sun. The novel revolves around Klara, an Artificial being/Friend designed to provide companionship and protection to humans. What the AI being doesn’t have that humans have? What does it mean to care for humans by non-humans? In the novel, Klara (Artificial Friend/AF) protects and provides companionship to Josieher friend and owner. Klara challenges the anthropocentric notion of humanity. She experiences and expresses human qualities and capabilities that accentuate Klara on a human level. By providing typical human qualities - love and compassion, sympathy and empathy, nostalgia, etc. – to Klara, Ishiguro fulfills the gap between the world of humanity and the world of AI/AF beings. This novel critiques such practices of anthropocentrism. Since the AI/AF beings exhibit supposedly human emotions; it transcends the setup boundary between them. Drawing on the theory of posthumanism forwarded by Donna Haraway, Rosi Braidotti, and N. Katherine Hayles, this paper attempts to analyze how the boundary between humans and Artificial Intelligence entities is blurred. These critics create a nonhuman platform to give place and position to the ‘others’. Incorporating qualitative paradigm and interpretive technique, this paper analyses lines and ideas from the primary text to support the arguments. As a library research it uses secondary sources from various platforms. The paper further envisions a world where traditional binaries like human/non-human can be deconstructed.